Current update on the visual outcome of optic pathway glioma associated with neurofibromatosis type-1 - Zeid, Janice Lasky (Frontiers in Surgery, 2022)
Purpose Clinical and diagnostic evaluation in the follow-up of optic glioma patients with neurofibromatosis type 1 (NF-1) can be difficult. Determining whether and when to provide treatment is a significant challenge in best managing these patients. Update on current information and future directions in management is included in this review. Current Practice NF-associated optic pathway gliomas (OPGs) present a significant management challenge with high stakes for visual outcomes. Monitoring vision and diagnostic tests are challenging in patients of a younger age. Regardless of whether few or many optic gliomas are encountered during clinical practice. Summary This review of optic gliomas-NF1-associated gliomas includes the current approach and knowledge of OPG-NF1 and future directions in OPG-NF1 management. This includes the ongoing Multicenter Natural History Study and other clinical trials and outcomes in NF-1 patients with OPG.